PENATAAN LEMBAGA NEGARA REFLEKSI PENGUATAN SISTEM PRESIDENSIAL - Abustan Abustan (Al-Adl, 2017)
The amendment of Article 1 Paragraph (2) of the 1945 Constitution of the Republic of Indonesia indicates the affirmation of Article 4 Paragraph (1) of the 1945 Constitution of the Republic of Indonesia, namely the affirmation of a presidential government system by affirming the position of the President as head of state as head of government of government) can not be separated and elected directly by the people, so that the President has the authority as "the sobereigh executive" to run "independent power" and "inherent power", while establishing the separation of power in establishing cheks and balances among state institutions. Prior to the amendment of the 1945 Constitution, the institutional system adopted is the separation of power but is often referred to as the distribution of power. The President not only holds the highest administrative power (executive but also holds the power to form legislation or legislative powers together with the DPR as his co-legislator, while the question of judicial power (judicial in the 1945 Constitution before changes are made by a Supreme Court and other judicial bodies according to the law. Given the change of power of the formation of a law which was originally owned by the President to be owned by the House of Representatives based on the amendment of the 1945 Constitution, especially Article 5 paragraph (1) and Pasa1 20 paragraph (1), the so-called legislative body (main) DPR, while the executive is the President. Although the process of making a law requires the approval of the President, but the function of the President in this case is as co-legislator as the DPD for the material of a particular law, not as the main legislator. While the judicial authority (judicative conducted by the Supreme Court (and the judicial bodies under it) and the Constitutional Court under Article 24 paragraph (2) of the 1945 NRI Constitution. Structuring the building of presidential government system, as well as other state institutions (DPR, MPR, DPD, MA and MK) within the framework of the 1945 Constitution of 1945 should be harmonized and synchronized to prevent the occurrence of various disorders among state institutions.